First-Year Students’ English Language Learning Anxiety: A Survey at Universitas Serambi Mekkah - Septhia Irnanda; Nora Fitria; Sabrina; Cut Mulia Zuhra; Zaiyana Putri (Universitas Serambi Mekkah, 2024)
English is a relatively difficult subject for Indonesian-speaking learners. The anxiety of learning English is reported to be associated with the level of English learning achievement. To understand the Universitas Serambi Mekkah students’ psychological states towards English learning in general, this study surveyed the first-year students’ English language learning anxiety using a questionnaire developed by Iwaniec (2014). This anxiety measuring tool uses five-point Likert-scale questions and consists of 8 items. The population was all new students of the 2023 Academic Year at Universitas Serambi Mekkah with a total number of 1264. There were 184 students from three faculties who participated in the survey. Findings from the eight statements regarding English language learning anxiety show that the first-year students of Universitas Serambi Mekkah in general have a relatively high level of anxiety in learning English. The classroom performance type of anxiety is higher than the academic-achievement one. This implies that the USM English language learners need a secure English learning environment to reduce their learning anxiety.